The symbiosis of the plastic image and the musical component in European painting - Rodica URSACHI (Dialogica: Revistă de Studii Culturale și Literatură, 2024)
The article deals with the aspect of the interrelationship between two related artistic fields under the “rhythmic” aspect – painting and music. This connection has been present in artistic manifestations since the beginning of human civilization and had a magical-religious character. Interest in musical aesthetics increases in the medieval period, but especially in the Renaissance when the arts gain a dominant role in society. The socio-political and religious changes in society in the century XVII-XVIII, impose an alert and dynamic rhythm, an increased interest in all spheres of artistic culture, including fine art and music. The musical component persists in plastic creation and in the century XIX-XX, in different styles or artistic currents. A particular predilection for musical subjects is observed in the representatives of romanticism and symbolism, visual artists making a “leap” from the sphere of the real, mundane world to mystical-fantastic or cosmic dimensions. The return of the artistic vision in everyday life is evident in subjects with human figures singing, dancing, etc. in realism, impressionism, post-impressionism, fauvism, etc. A special plastic formula of the musical component in painting is present in the creation of abstractionists, expressionists who “see” musical sounds in color. In the Romanian-Bessarabian space, the musical theme is found in various thematic works, of a static nature, but with a generally relatively low frequency.